Hot tapping process analysis on gas distribution pipes online service using Shielded Metal Arc Welding - Budi Prasojo; Yunan Sadli Nasution; Endah Wismawati; Subagio So’im; M. Ari (Politeknik Negeri Lhokseumawe, 2022)
In a piping system makes it possible to add branching into an existing piping system. In this research will discuss about installation 12